2007
DOI: 10.1155/2007/19469
|View full text |Cite
|
Sign up to set email alerts
|

The Protecting Effects and Mechanisms of Baicalin and Octreotide on Heart Injury in Rats with SAP

Abstract: Purpose. To observe the protecting effects and mechanisms of Baicalin and Octreotide on heart injury in rats with severe acute pancreatitis (SAP). Methods. The SAP rat models were randomly divided into the model group, Baicalin-treated group, Octreotide treated group, and sham operation group. The contents of some inflammatory indexes in blood were determined. The rat mortality, pathological changes of heart, the changes of NF-κB, P-Selectin, Bax, Bcl-2, and Caspase-3 protein expression levels as well as apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…A previous report confirmed that baicalin could have a protective effect on heart injury in rats with severe acute pancreatitis. 22) Baicalin has also shown potent protection against ischemia/reperfusion injury in cultured chick cardiomyocytes. 23) In the cultured rat cardiomyocytes exposed to hypoxia/reoxygenation, baicalin treatment effectively inhibited the nuclear translocation of NF-κB and exerted cardioprotective efficacy.…”
Section: Effects Of Baicalin On the Caspase-3 Protein And Mapk Cascadmentioning
confidence: 99%
“…A previous report confirmed that baicalin could have a protective effect on heart injury in rats with severe acute pancreatitis. 22) Baicalin has also shown potent protection against ischemia/reperfusion injury in cultured chick cardiomyocytes. 23) In the cultured rat cardiomyocytes exposed to hypoxia/reoxygenation, baicalin treatment effectively inhibited the nuclear translocation of NF-κB and exerted cardioprotective efficacy.…”
Section: Effects Of Baicalin On the Caspase-3 Protein And Mapk Cascadmentioning
confidence: 99%
“…Experimental Medicine and Reagents [13][14][15][16] Sodium taurocholate and sodium pentobarbital obtained from Sigma Company (USA); Octreotide obtained from Novartis pharmaceutical company (Swiss); 5% Baicalin injection prepared by the first author (China national invention patent number ZL200310122673.6). The NF-κB p65 and P-Selectin antibody obtained from Santa Cruz Company (USA).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Several groups reported that baicalin induced apoptosis of cancer cells [46] and carcinoma cells [47], via ERK and p38 MAPK signaling pathways. However, baicalin also showed cytoprotective effects on CMs [48,49], hepatocytes and neural cells [50,51,52]. A latest study reported that baicalin attenuates acute myocardial infarction of rats via mediating ERK and p38 MAPK signaling pathways [48].…”
Section: Discussionmentioning
confidence: 99%